NEW APPROACH TO THE STUDY OF THE RESULTS OF HYDRAULIC FRACTURING (ON THE EXAMPLE OF BOBRIKOVSKY DEPOSITS OF THE SHERSHNEVSKY FIELD) - Vladislav I. Galkin; Inna N. Ponomareva; Sergey S. Cherepanov; Evgeniy V. Filippov; Dmitriy A. Martyushev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2020)
The relevance of the researchis caused by significant contribution of oil produced as a result of hydraulic fracturing at the wells to its total production. Correct assessment of the results of actually carried out measures for hydraulic fracturing will make it possible to develop clear recommendations on the further application of this method of intensifying oil production for geological and physical conditions of specific fields. The main aim of the research isto evaluate the effect of hydraulic fracturing in relation to the element of the development system in which the well is located – the object of impact. Object: oil producing wells that make up an element of the reservoir development system. Method: geological field research, correlation analysis, schematization of the interaction between wells. Results. It was found that the hydraulic fracturing of the well 221 of the Shershnevskyfield led to a change in the nature of interaction between the wells within the entire element of the development system, which began to work as a single, unidirectional coordinated system. As a result of hydraulic fracturing, there was no redistribution of drainage volumes, but a synergistic effect arose when holding an event in one well led to an increase in flow rates and consistency of the entire element of the development system. Probably, the conduction of hydraulic fracturing in the well 221 led to a significant change in the reservoir filtration parameters in more significant limits than the volume of the drainage zone of this well, and rather large system of channels with reduced filtration resistance appeared in rather large area of ​​the reservoir, as it is customary in classic presentation.